Application of Aptamers in Virus Detection and Antiviral Therapy - Zou, Xinran; Wu, Jing; Gu, Jiaqi; Shen, Li; Mao, Lingxiang (Frontiers in Microbiology, 2019)
Viral infections can cause serious diseases for humans and animals. Accurate and early detection of viruses is often crucial for clinical diagnosis and therapy. Aptamers are mostly single-stranded nucleotide sequences that are artificially synthesized by an in vitro technology known as the Systematic Evolution of Ligands by Exponential Enrichment (SELEX). Similar to antibodies, aptamers bind specifically to their targets. However, compared with antibody, aptamers are easy to synthesize and modify and can bind to a broad range of targets. Thus, aptamers are promising for detecting viruses and treating viral infections. In this review, we briefly introduce aptamer-based biosensors (aptasensors) and describe their applications in rapid detection of viruses and as antiviral agents in treating infections. We summarize available data about the use of aptamers to detect and inhibit viruses. Furthermore, for the first time, we list aptamers specific to different viruses that have been screened out but have not yet been used for detecting viruses or treating viral infections. Finally, we analyze barriers and developing perspectives in the application of aptamer-based virus detection and therapeutics.